Financial structure and the interest rate channel of ECB monetary policy - Benoît Mojon (European Central Bank (ECB), 2000)
This paper analyses persistence differences in financial structure across countries of the euro area and whether they can lead to asymmetries in the transmission of the ECB policy. First, the paper examines the pass-through of money market rates to various bank retail rates and measures how this has evolved over the past two interest rate cycles. An analysis of panel data suggests that current 'country asymmetries' in the response of bank rates to monetary policy should decrease over time by virtue of the implementation of the single monetary policy, money market integration and the growth of debt securities markets and competition among banks. Second, analysis of the balance sheet structure of households and firms shows that the income effects of monetary policy are fairly homogenous in the four largest countries of the euro area, while wealth effects could be stronger in Italy.
Keywords: E43; E52; G21; 330; financial structure and the interest rate